DEVELOPING BENCHMARKING AND CONTROL POINTS FOR THE ELECTRICAL OVERHEAD TRANSMISSION CONSTRUCTION INDUSTRY - Ripp, Roger (My University, 2016)
Abstract: The Electrical Transmission Construction Industry is a vital piece of the integrated system that aims to supply reliable and cost effective power to end load use customers, residential and commercial. New infrastructure has grown from a 9 billion dollar industry in 2008 to approximately 20 billion dollar industry in 2014. It is considered a high risk industry due to the high percentage of labor costs. It is important for owners and contractors in this industry to track labor performance to optimize and execute projects effectively. In this paper, benchmark indicators for this industry are established to study the relationship between the percent complete of the project duration and the cumulative man-hours. This relationship was developed using regression analysis and strong statistical trends where observed to generate manpower loading curves, S-Curves, cost performance index, and other earned value tools using a significant number of 10 projects. The projects were extracted from one owner and two contractors in the Upper-Midwest of the United States. The electrical overhead (OH) transmission line construction industry was broken down into different work areas and tasks. The analysis was performed at both the project level and the task level. The results were then used as a reference to evaluate the labor performance of a different project. The specific industry benchmarks will assist Project Managers in reviewing labor plans and measuring and identifying labor productivity issues.